Exterior analysis: using applications of differential forms - Suhubi, Erdogan S., 1934- (Academic Press, 2013)
Exterior analysis uses differential forms (a mathematical technique) to analyze curves, surfaces, and structures. Exterior Analysis is a first-of-its-kind resource that uses applications of differential forms, offering a mathematical approach to solve problems in defining a precise measurement to ensure structural integrity. The book provides methods to study different types of equations and offers detailed explanations of fundamental theories and techniques to obtain concrete solutions to determine symmetry. It is a useful tool for structural, mechanical and electrical engineers, as well as physicists and mathematicians. Provides a thorough explanation of how to apply differential equations to solve real-world engineering problems. Helps researchers in mathematics, science, and engineering develop skills needed to implement mathematical techniques in their researchIncludes physical applications and methods used to solve practical problems to determine symmetry.